Ceftazidime–avibactam Susceptibility Patterns in Carbapenem-Resistant Enterobacteriaceae in the USA: Results from the Consortium on Resistance against Carbapenems in Klebsiella and Other Enterobacteriaceae (CRACKLE-2). (4th October 2017) - Van Duin, David; Humphries, Romney; Jacob, Jesse T; Cober, Eric; Richter, Sandra S; Doi, Yohei; Kaye, Keith S; Dhar, Sorabh; Arias, Cesar; Kim, Angela; Garcia-Diaz, Julia; Han, Jennifer H; et al.
Abstract: Background: Ceftazidime–avibactam (caz-avi) is a new treatment option for carbapenem-resistant Enterobacteriaceae (CRE). Methods: The Consortium on Resistance Against Carbapenems in Klebsiella and other Enterobacteriaceae (CRACKLE-2) is a multi-center, prospective, observational study of 60 hospitals in all five regions of the USA. Hospitalized patients with CRE isolated from clinical cultures are enrolled in CRACKLE-2. CRE was defined per CDC guidelines. Pitt Bacteremia score (PBS) and Charlson comorbidity score (CMS) were calculated. caz–avi susceptibility was tested as clinically indicated in participating clinical laboratories. Results: From June 1, 2016–April 4, 2017, 568 unique patients with 591 admissions and 681 culture episodes (42% infection, 58% colonization) were included. The distribution of 252 first CRE infections per unique patient was 78 (31%) blood, 67 (27%) urine, 37 (15%) respiratory, 34 (13%) intra-abdominal, 30 (12%) wound, and 6 (2%) other. Patients with CRE infections were chronically ill (CMS median [IQR] 3 [1, 5]) and acutely ill (PBS median [IQR] 3 [2, 6]). Outcomes were available for 198 patients with infections; all-cause mortality was 29/198 (15%) at 14 days, and 55/198 (28%) at 90 days. K. pneumoniae (62%), E. cloacae (17%), and E. coli (13%) were the top three CRE species. A total of 124 isolates were tested for carbapenemase genes; 62/124 (50%), and 29/124 (23%) were positive for blaKPC-2, and blaKPC-3, respectively. Within 96 tested CR K. pneumoniae (CRKP) isolates, 22/96 (23%), 36/96 (38%), 38/96 (40%) were ST258-1, ST258-2, and non-ST258 clades, respectively. Antibiotic data were available for 224 patients with infections. In various combinations, 37/224 (16%) patients received polymyxins, 74/224 (33%) aminoglycosides, 111/224 (49%) carbapenems, 47/224 (21%) ceftazidime/avibactam, and 26/224 (12%) tigecycline. A total of 111 CRE were tested for caz–avi susceptibility; 32/111 (29%) were non-susceptible. All-cause mortality by caz–avi susceptibility did not differ among 62 patients with outcomes ( P =  0.74). Conclusion: In this national sample of hospitalized patients with CRE, 29% of tested isolates were caz–avi non-susceptible. Results need to be confirmed by central laboratory testing. Disclosures: D. Van Duin, Astellas: Scientific Advisor, Consulting fee. Achaogen: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. MedImmune: Scientific Advisor, Consulting fee. Shionogi: Scientific Advisor, Consulting fee. S. S. Richter, bioMerieux: Investigator, Research support. BD Diagnostics: Investigator, Research support. Roche: Investigator, Research support. BioFire: Investigator, Research support. OpGen: Investigator, Research support. K. S. Kaye, Xellia: Consultant, Consulting fee. Merck: Consultant and Grant Investigator, Consulting fee and Research support. The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support. C. Arias, Bayer Global: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. Medicines Company: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium. Pfizer: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium. Allergan: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium.